Ensino de cônicas - Domingues, Ana Clara de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Among the mathematical content, conics is seen briefly, according to the Common National Curriculum Base. However, among the aspects of mathematics, perhaps it is quite present in our daily lives. We can find their curves in receiving paraboloids like satellite dishes or emitters like lanterns, we can find them in the path of celestial elements like planets, asteroids and satellites or particles in the electric field. Its study can be applied in several areas of knowledge, such as architecture, astronomy, physics, engineering, etc. Seeing how important this content is, this work’s objective is to facilitate the Teaching of Conics through an auxiliary text, structured with its theory, historical context, examples, exercises and application in everyday life. We will also use GeoGebra software and Concrete Material, in order to make learning more attractive.

Entre os conteúdos de matemática, cônicas é visto de forma breve, de acordo com a Base Nacional Comum Curricular. Porém entre as vertentes da matemática, talvez ele seja bastante presente em nosso dia a dia. Podemos encontrar suas curvas em paraboloides receptores como antenas parabólicas ou emissores como lanternas, podemos encontrá-las no trajeto de elementos celestes como planetas, asteroides e satélites ou de partículas no campo elétrico. O seu estudo pode ser aplicado em várias áreas do conhecimento, como arquitetura, astronomia, física, engenharia, e etc. Vendo o quão importante é esse conteúdo, temos como objetivo deste trabalho facilitar o Ensino de Cônicas por meio de um texto auxiliar, estruturado com sua teoria, contexto histórico, exemplos, exercícios e aplicação no dia a dia. Utilizaremos também o software GeoGebra e Material Concreto, com o intuito de tornar o aprendizado mais atrativo.
Teaching of conics
Keywords: Conical; Hyperbole; Parable; Cônicas; Elipse; Hipérbole; Parábola; GeoGebra; Ellipse